Directivity improvement of microstrip antenna by inverse refraction metamaterial - Tutuncu, Bilal; Torpi, Hamid; Imeci, S. Taha (ACADEMIC PUBLICATION COUNCIL, 2019)
Due to the properties of inverse refraction, the metamaterials can focus the incident wave and can be used as a lens for high directive antennas. For this purpose, in this study, initially, a metamaterial unit cell is designed to exhibit metamaterial feature at 12 GHz and converted into a periodic layer. The reference antenna and the proposed metamaterial layers are simulated and fabricated. It is observed that the directivity of the reference antenna is increased by 2.74 dB with one layer of the proposed metalayer according to the measurement results. Finally, a double lens layer is used and an increase of 4.08 dB is observed. In the literature, the dimensions of metalayers, that is, used to achieve directivity enhancement, are larger than the patch size, but in this study we achieve a significant improvement with metalayers that have almost the same dimensions as the patch. However, the proposed antenna system is more effective than Ku-band antennas in the literature due to its high directivity compared to similar ones.
Keywords: Metamaterial; microstrip patch antenna; LHM; antenna directivity; OMEGA; Engineering